Reasons Underlying a Wife's Divorce Suit at the Sungguminasa Religious Court, South Sulawesi: An Islamic Law Philosophy Perspective - Halim, Patimah; Idrus, Achmad Musyahid; Mustafa, Adriana; Herawati, Andi; Asti, Mulham Jaki (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This study examines the reality of divorce litigation at the Sungguminasa Religious Court in Gowa, the underlying reasons wives initiate divorce, and public perceptions regarding divorce proceedings at the court. It also explores the philosophical rationale of Tasri's approach in relation to the benefits of divorce litigation. Employing an empirical legal method, the study analyzes data through the lens of mashlahat theory and Islamic legal philosophy, using a case study approach based on divorce records from the court. Data were collected through in-depth interviews and document analysis, including court decisions. The findings reveal that the primary reasons wives file for divorce are closely linked to their welfare, which can be classified into three levels: darūriyyāt (essential), ḥājiyyāt (complementary), and taḥsīniyyāt (enhancing) welfare. Domestic violence (KDRT) represents a darūriyyāt welfare concern, as it threatens a wife's life and well-being. Biological needs reflect , ḥājiyyāt welfare, prompting wives to seek divorce to fulfill essential personal needs. Economic sufficiency is associated with taḥsīniyyāt welfare, contributing to the completeness of a wife's social and family life. Finally, the study notes a rising trend in divorce cases filed at the Sungguminasa Religious Court between 2021 and 2023.